Intentos gubernamentales por proteger el derecho al trabajo en un Estado de Emergencia: análisis de la racionalidad de las circulares no. 021 y no. 022 del Ministerio del Trabajo (2020)
A State of Economic, Social and Health Emergency can impact labor relations and its components. The actions that the State can carry out could fail to reach the needs that demand to be solved. A government attempt to protect employment during the emergency consisted in the expedition of Circulars No. 021 and No. 022, by the Ministry of Labor, on March 17 and 19, respectively. These government actions are just one example of regulations issued in times of emergency. However, when it comes to the Executive branch as an entity empowered to regulate exceptionally, its normative attempts can present challenges in its rationality. This, in part, is due to the urgency required to act in such challenging times that it may go through. It is possible, therefore, that regulations present gaps, do not possess sufficient capacity to motivate the conduct, presents a lack in providing the necessary means to achieve a certain end, or even could have lack of effectiveness - by not providing clear legal consequences-. And this makes that the degree of compliance of the constitutional objective -that has already been set- decrease significantly. Besides, despite the fact that the State may choose to protect and comply with the constitutional principles formally, the obstacles that are presented to the institutional design in its rationality, keep it from the material fulfillment of those objectives. Indeed, government action plays an important role in reducing the impact that a crisis can have on employment and on the citizens' right to work. For this reason, their actions must be aligned, not only in theory but also in practice, with what the Colombian legal system by the 1991 National Constitution has provided for the effective protection of the right to work of its citizens.